1988
DOI: 10.1177/019251388009001005
|View full text |Cite
|
Sign up to set email alerts
|

Female Autonomy, the Family, and Industrialization in Java

Abstract: It is generally argued that industrialization has an adverse affect on the position of women due to their exclusion from industrial employment and the resultant erosion of their status. This article addresses a case study to the question of gender stratification and industrialization by analyzing the relationship between factory daughters and their families in Java, Indonesia. The case study suggests that industrialization at the very least maintains, and may even enhance, female status within the family. I co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Despite this, Wolf (1988) found that the factory women she interviewed saved, on average, 30% of their income for use to redistribute to families in times of distress or to finance their own weddings. These studies suggest that cultural factors influence gendered saving behaviour, and cross-country variations are likely to be important.…”
Section: Gendered Determinants Of Saving Preferencesmentioning
confidence: 96%
“…Despite this, Wolf (1988) found that the factory women she interviewed saved, on average, 30% of their income for use to redistribute to families in times of distress or to finance their own weddings. These studies suggest that cultural factors influence gendered saving behaviour, and cross-country variations are likely to be important.…”
Section: Gendered Determinants Of Saving Preferencesmentioning
confidence: 96%
“…First, jobs created by industrialization often detract from the status of women by eliminating craft production and replacing economic niches held by women. Wolf (1988) contended, however, that the availability of wage employment has improved that status of women in Java. Second, improved economic status may facilitate divorce for women, as has been argued regarding Western societies.…”
Section: Forces Of Changementioning
confidence: 99%
“…Given such poverty, 1 expected high remittances from factory wages to the family economy, an expectation strengthened by empirical research from all over the world on factory daughters and the family economy (Arrigo, 1980;Dublin, 1979;Hareven, 1982;Ong, 1987;Tilly and Scott, 1978;Salaff, 1981). My findings of a high degree of income retention rather than income pooling have been documented elsewhere (Wolf, 1988b). Unlike their Taiwanese counterparts who turn over 50 to 80 per cent of factory wages to families, these Javanese factory daughters controlled their own income, remitting little if anything from their weekly wages to the family till, and often asked their parents for money.…”
Section: Motives For Seeking Factory Employmentmentioning
confidence: 54%